Study of heat transfer in plate heat exchanger by using CFD simulation - Wan Nurmaisarah, Wan Hamaruddin (2012)
A plate heat exchanger is a type of heat exchanger which uses metal plates to transfer heat between two fluids.The metal plates that commonly used are stainless steel because of its ability to withstand high temperatures, its strength and its corrosion resistance.The basic working principle is very simple though;the channels that formed between the plates and corner ports are arranged so that the two fluid flows through alternate channels.The heat is transferred through the thin plate between the channels,and creating complete counter current flow for highest possible efficiency.No intermixing of the fluid or leakage to the surroundings will occur as gaskets around the edges of the plates seal the unit.The objectives of this study are to study the heat transfer performance of plate heat exchanger for heating diesel with hot water and to observe which configurations and parameters that gives the best results. In addition,the objective is to study and modeling the heat transfer of plate heat exchanger using simulation. Computational Fluid Dynamic(CFD)is a tool used in this simulation which consists of GAMBIT and FLUENT.Volume meshing in GAMBIT is an important part to be considered before doing simulation in FLUENT as a solver.Parameters that had been used were velocity and temperature of water. The velocity for both diesel and hot water were calculated using mass flow rate of 100L/min,150 L/min and 200L/min as a basic. The temperature of hot water varies from 60°C, 70°C and 80°C.Thus,this paper presents the simulation of heat transfer in plate heat exchanger model for parallel and series configurations.It is observed that lower velocity and high temperature of water gives better heat transfer performance.Parallel configuration is selected for the best configuration in this study.